Efecto de la temperatura sobre el crecimiento de juveniles de Petenia kraussii (Pisces:Cichlidae): Relación ARN/ADN - Lemus, M. J. (1993)
We determined the instantaneous growth rate (RNA/DNA ratio) in juvenile Pelenia kraussii exposed during four weeks at 22 and 30°C. The RNA and protein levels were significantly greater (P<0.001) in samples exposed at 22°C than in those at 30°C. The RNA/DNA ratios during four week-experimental periods were three times higher in fish exposed at 22°C than in those at 30°C, suggesting a better physiological condition at low temperatures for P. kraussii.